Risperidone ISM: review and update of its usefulness in all phases of schizophrenia - Thomas Messer; Miquel Bernardo; Lourdes Anta; Javier Martínez-González (SAGE Publishing, 2024)
One of the most important challenges in the management of patients with schizophrenia is to ensure adherence to antipsychotic treatment. The contribution of long-acting injectables (LAI) is undeniable in this matter, but there are still some unmet medical needs not covered by these drugs (e.g. quick onset of action for patients with acute exacerbation of schizophrenia). This article summarises the pharmacokinetics, efficacy and safety of Risperidone ISM ( in situ microparticles). The aim of this review is to provide information about the potential uses of this new LAI formulation of risperidone for the treatment of schizophrenia, contextualising and diving into the published evidence. Risperidone ISM shows a rapid release which allows achieving within 12 h risperidone active moiety levels similar to those observed in the steady-state for oral risperidone treatment, achieving a mean average concentration of 38.63 ng/mL. The plasma concentration of active moiety achieved by Risperidone ISM comes with a predictable dopamine D2 receptor occupancy above 65% throughout the 28-day dosing period, which is accepted as a threshold for the efficacy of the antipsychotic treatment. This can be associated with the positive efficacy findings throughout its clinical development. In the short term, it provides an early and progressive reduction of symptoms in adult patients with acute exacerbation of schizophrenia without the need for loading doses or oral risperidone supplementation, which could contribute to reinforcing the therapeutic alliance between the patient and the psychiatrist. In addition, long-term treatment was effective, safe and well tolerated regardless of the initial disease severity or whether patients were previously treated with Risperidone ISM during an acute exacerbation or switched from stable doses of oral risperidone. Improvement and maintenance of personal and social functioning and health-related quality of life were observed in each setting, respectively. All these findings endorse Risperidone ISM as a useful and valuable treatment for the acute and maintenance management of patients with schizophrenia.